Using Behavioral Insights to Improve School Administrative Communications: The Case of Truancy Notifications. (October 2021) - Lasky-Fink, Jessica; Robinson, Carly D.; Chang, Hedy Nai-Lin; Rogers, Todd
Many states mandate districts or schools notify parents when students have missed multiple unexcused days of school. We report a randomized experiment ( N = 131, 312) evaluating the impact of sending parents truancy notifications modified to target behavioral barriers that can hinder effective parental engagement. Modified truancy notifications that used simplified language, emphasized parental efficacy, and highlighted the negative incremental effects of missing school reduced absences by 0.07 days in the 1 month following compared to the standard, legalistic, and punitively worded notification—an estimated 40% improvement over the standard truancy notification. This work illustrates how behavioral insights and randomized experiments can be used to improve administrative communications in education.